2014
DOI: 10.1159/000362435
|View full text |Cite
|
Sign up to set email alerts
|

Instant Reocclusion following Mechanical Thrombectomy of in situ Thromboocclusion and the Role of Low-Dose Intra-Arterial Tirofiban

Abstract: Background: An in situ thromboocclusion (IST) is defined as an infarct extensively involving all or most of a stenosed arterial territory, which is one major stroke mechanism related to intracranial atherosclerosis (ICAS). We focused on ISTs occurring in major cerebral arteries and analyzed their rate of instant reocclusion during mechanical thrombectomy (MT) compared with non-ISTs. Also, we introduced a treatment strategy of low-dose intra-arterial tirofiban administration to prevent such reocclusion followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(192 citation statements)
references
References 18 publications
8
179
0
Order By: Relevance
“…Although the optimal treatment for underlying ICAS in patients presenting with hyperacute stroke remains unknown, 21 the identification of underlying ICAS before endovascular therapy could help interventionists make appropriate therapeutic decisions. 5,18,22 Recently, Kang et al 22 reported that patients with underlying ICAS who presented with acute stroke had an increased tendency for instant reocclusion of the treated arteries after the initial mechanical thrombectomy. They suggested that the infusion of intra-arterial antiplatelet agents in combination with a thrombolytic agent might reduce the rate of reocclusion in pa- tients with acute stroke with underlying ICAS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the optimal treatment for underlying ICAS in patients presenting with hyperacute stroke remains unknown, 21 the identification of underlying ICAS before endovascular therapy could help interventionists make appropriate therapeutic decisions. 5,18,22 Recently, Kang et al 22 reported that patients with underlying ICAS who presented with acute stroke had an increased tendency for instant reocclusion of the treated arteries after the initial mechanical thrombectomy. They suggested that the infusion of intra-arterial antiplatelet agents in combination with a thrombolytic agent might reduce the rate of reocclusion in pa- tients with acute stroke with underlying ICAS.…”
Section: Discussionmentioning
confidence: 99%
“…Significant stenosis was defined according to the following criteria: 1) degree of fixed stenosis of Ͼ70%, 19 or 2) moderate stenosis with either flow and perfusion impairment on angiography or an evident tendency toward reocclusion, 13 even after sufficient primary endovascular treatment was performed. Underlying IAD can be observed from partial recanalization spontaneously or after intravenous thrombolytic treatment, but these cases were excluded in this study because primary thrombectomy devices for intracranial occlusions were allowed.…”
Section: Patientsmentioning
confidence: 99%
“…If reperfusion was not achieved or the occlusion was sustained, we applied rescue treatments, including the switching strategy, 22 angioplasty, 23 stent placement, 24 and intra-arterial tirofiban infusion, 13 with consensus from the neurointerventionalist and neurologist. Follow-up angiography was performed 10 -20 minutes after recanalization.…”
Section: Acute Stroke Management Protocol and Endovascular Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 The etiology of acute LAO seems related to stent retriever refractoriness and some other complications, such as inadvertent detachment, stent retrievers getting stuck, and frequent reocclusions. [19][20][21][22] The presence of truncal-site occlusion reflecting intracranial atherosclerosis was associated with a lower chance of stent retriever success, and these patients more frequently required adjunctive therapies, such as stent placement or use of glycoprotein IIb/IIIa inhibitors. 4 Failure of stroke intervention was associated with longer procedural times and delayed recanalization, resulting in larger infarct volumes and worse neurologic outcomes.…”
Section: Discussionmentioning
confidence: 99%